Corrosion-resistant self-cleaning aluminum alloy and preparation method thereof

By using nanotitanium dioxide-loaded microparticles and yttrium oxide submicron fiber composite filler in aluminum alloy materials, a material with three-dimensional and micro-nano structure is formed, which solves the corrosion and pollution problems of aluminum alloy materials, and achieves corrosion resistance and self-cleaning effects.

CN119506740APending Publication Date: 2025-02-25SHANDONG INNOVATION PRECISION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411541061.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing aluminum alloy materials are prone to corrosion and contamination during use, and the preparation of micro-nano structures has problems such as complex operation, poor controllability and low efficiency, making it difficult to achieve corrosion resistance and self-cleaning effects.

Method used

The composite filler with nanotitanium dioxide-loaded microparticles and yttrium oxide submicron fibers are used to mix it with the aluminum alloy substrate by electromechanical stirring to form an aluminum alloy material with a three-dimensional structure and a micro-nano structure.

Benefits of technology

It improves the hydrophobicity and self-cleaning effect of the aluminum alloy surface, enhances the corrosion resistance of the material, reduces the generation of cracks, and improves the catalytic activity and stability of nano-titanium dioxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112805360000051
    Figure BDA0005112805360000051
  • Figure BDA0005112805360000061
    Figure BDA0005112805360000061
  • Figure BDA0005112805360000081
    Figure BDA0005112805360000081
Patent Text Reader

Abstract

The invention provides a corrosion-resistant self-cleaning aluminum alloy and a preparation method thereof.The preparation method comprises the following steps that S1, an aluminum alloy base material is heated to be molten, nanometer titania-loaded micron particles and yttrium oxide submicron fibers are added, and an electric mechanical stirrer is adopted for stirring; and S2, casting into a mold. According to the invention, the filler compounded by nano titanium dioxide-loaded micron particles and yttrium oxide submicron fibers is used, the nano titanium dioxide-loaded micron particles are of a three-dimensional structure, are formed by mutual winding and penetration in a three-dimensional space, can transfer and disperse stress among phases and prevent crack propagation, and have a micron structure, so that the nano titanium dioxide-loaded micron particles and yttrium oxide submicron fibers are compounded, and the nano titanium dioxide-loaded micron particles can be used for preparing a composite material. And a micro-nano structure is formed with the loaded nano titanium dioxide, so that the hydrophobicity of the surface of the aluminum alloy is enhanced, and the self-cleaning effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum alloy materials, and in particular to a corrosion-resistant self-cleaning aluminum alloy and a preparation method thereof. Background Art

[0002] As a widely used engineering material, aluminum alloy has excellent properties such as light weight, high specific strength and easy recycling. It is particularly important in industries such as shipbuilding, aviation, automobiles, electricity, and construction, and has become one of the important pillar materials for the development of the national economy. Self-cleaning, corrosion resistance and other technical problems in these fields need to be solved urgently, and they are closely related to the structural characteristics of the materials and the selection of fillers. By selecting fillers, adding anti-corrosion fillers, such as ceramic particles, can effectively prevent medium corrosion. In nature, the excellent hydrophobicity and self-cleaning properties of lotus leaves are mainly caused by the countless micron-sized papillary structures distributed on the surface of lotus leaves and the nanoparticles attached to them. This structure is conducive to increasing the amount of air trapped, forming an air film layer on the surface of the leaves, and greatly reducing the attachment of dust and other dirt. Inspired by this, the preparation of micro-nano structure surfaces has become a research hotspot in interdisciplinary fields. By changing the behavior of the surface / interface, new functional properties can be given to materials, so it has attracted much attention. At present, the preparation of micro-nano structures generally has problems such as complex operation, poor controllability, and low efficiency, and there are obvious deficiencies in the theoretical design and controllable preparation of micro-nano structures. How to improve the corrosion resistance and self-cleaning effect of aluminum alloy by designing its surface structure and adding fillers is the problem that this patent needs to solve. Summary of the invention

[0003] Technical problem to be solved: In view of the above technical problems, the purpose of the present invention is to provide a corrosion-resistant self-cleaning aluminum alloy and a preparation method thereof, which adopts a composite filler of micron particles loaded with nano-titanium dioxide and yttrium oxide submicron fibers. The micron particles loaded with nano-titanium dioxide have a three-dimensional structure, which is formed by mutual entanglement and penetration in three-dimensional space. It can transfer and disperse the stress between phases and prevent the expansion of cracks. It also has a micron structure and forms a micro-nano structure with the loaded nano-titanium dioxide, thereby enhancing the hydrophobicity of the aluminum alloy surface and improving the self-cleaning effect.

[0004] Technical solution: A method for preparing a corrosion-resistant self-cleaning aluminum alloy, comprising the following steps: S1: heating the aluminum alloy substrate until it is melted, adding micron particles loaded with nano-titanium dioxide and yttrium oxide submicron fibers, and stirring with an electric mechanical stirrer; S2: Cast into a mold. Furthermore, the aluminum alloy substrate includes the following components: Ni: 2.5-2.7%, Zn: 1.0-2.0%, Mg: 0.6-1.1%, Fe: 0.5-1.0%, B: 0.2-0.5%, other inevitable impurities: <0.2%, and the balance is Al. Furthermore, the particle size of the micron particles loaded with nano-titanium dioxide is 10-100 μm, and the micron particles have pore sizes of 80-120 nm and 1-30 μm. Furthermore, the diameter of the yttrium oxide submicron fiber is 100-300 nm, and the length is 1-10 μm. Furthermore, the mass ratio of the aluminum alloy, the micron particles loaded with nano-titanium dioxide and the yttrium oxide submicron fibers is 100:(5-10):(1-3). Furthermore, the preparation method of the micronized particles loaded with nano-titanium dioxide is as follows: (1) heating and melting 1 part of phenol, adding 60 parts of sodium carbonate solution with a mass concentration of 0.05 g / L and keeping the temperature for 10 minutes, adding 1.4 parts of formaldehyde solution, heating to 70° C. within 15 minutes, keeping the temperature for 20 minutes, heating to 95-98° C., keeping reflux boiling for 45 minutes, and immediately cooling to 80° C. to obtain a phenolic resin prepolymer solution; (2) adding 0.8-1 parts of polyvinyl alcohol to 40 parts of deionized water, stirring at 85° C. for 2 hours to obtain a polyvinyl alcohol solution; (3) mixing the phenolic resin prepolymer solution, the polyvinyl alcohol solution and 2-5 parts of nano-titanium dioxide with ultrasonic stirring for 0.5 h, and placing in an oven at 85° C. for 3 days to obtain a gel; (4) washing the gel with deionized water and ethanol in turn, and freeze-drying for 48 hours to obtain a precursor; (5) The precursor and potassium hydroxide are mixed and ground, placed in a tube furnace, and treated at 750° C. for 2 h in a N2 atmosphere; (6) washed with dilute HCl until neutral, dried, ground, and sieved to obtain micronized particles loaded with nano-titanium dioxide. Furthermore, the mass ratio of the precursor to potassium hydroxide is 1:1. The corrosion-resistant self-cleaning aluminum alloy prepared by the above method. Beneficial effects: 1. The present invention adopts a composite filler of micron particles loaded with nano-titanium dioxide and yttrium oxide submicron fibers. The micron particles loaded with nano-titanium dioxide have a three-dimensional structure, which is formed by mutual entanglement and penetration in three-dimensional space, and can transmit and disperse the stress between each phase, prevent the expansion of cracks, and have a micron structure, forming a micro-nano structure with the loaded nano-titanium dioxide, thereby enhancing the hydrophobicity of the aluminum alloy surface and improving the self-cleaning effect. 2. The micron particles of the present invention have a hierarchical pore structure, which is convenient for loading nano-titanium dioxide, and due to its unique pore structure and large specific surface area, it can improve the catalytic activity and stability of nano-titanium dioxide; at the same time, the porous structure can compress the space under pressure and reduce the generation of cracks in the aluminum alloy. 3. The yttrium oxide submicron fiber added in the present invention has a two-dimensional structure, which can be further dispersed with the micron particles to form a network structure, and its point-line structure can further improve the surface hydrophobic effect. 4. The present invention uses ultrasonic stirring to prepare nano-titanium dioxide-loaded micron particles, which can make the nano-titanium dioxide dispersed evenly and generate tiny bubbles to form a more dense porous structure of the gel. DETAILED DESCRIPTION The present invention proposes a corrosion-resistant self-cleaning aluminum alloy and a preparation method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention will be further described in detail with reference to the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Example 1 The preparation method of micron particles loaded with nano titanium dioxide is as follows: (1) heating and melting 1 part of phenol, adding 60 parts of sodium carbonate solution with a mass concentration of 0.05 g / L and keeping the temperature for 10 minutes, adding 1.4 parts of formaldehyde solution, heating to 70° C. within 15 minutes, keeping the temperature for 20 minutes, heating to 98° C., keeping reflux boiling for 45 minutes, and immediately cooling to 80° C. to obtain a phenolic resin prepolymer solution; (2) adding 0.8 parts of polyvinyl alcohol to 40 parts of deionized water and stirring at 85° C. for 2 h to obtain a polyvinyl alcohol solution; (3) mixing the phenolic resin prepolymer solution, the polyvinyl alcohol solution and 4 parts of nano-titanium dioxide with ultrasonic stirring for 0.5 h, and placing in an oven at 85° C. for 3 days to obtain a gel; (4) washing the gel with deionized water and ethanol in turn, and freeze-drying for 48 hours to obtain a precursor; (5) The precursor and potassium hydroxide in a mass ratio of 1:1 were mixed and ground, placed in a tube furnace, and treated at 750°C for 2 h in a N2 atmosphere; (6) washing with dilute HCl until neutral, drying, grinding, and sieving to obtain nano-titanium dioxide-loaded micron particles with a particle size of 10-100 μm. The micronized particles have pore sizes of 80-120 nm and 1-30 μm. Example 2 The preparation method of micron particles loaded with nano titanium dioxide is as follows: (1) heating and melting 1 part of phenol, adding 60 parts of sodium carbonate solution with a mass concentration of 0.05 g / L and keeping the temperature for 10 minutes, adding 1.4 parts of formaldehyde solution, heating to 70° C. within 15 minutes, keeping the temperature for 20 minutes, heating to 98° C., keeping reflux boiling for 45 minutes, and immediately cooling to 80° C. to obtain a phenolic resin prepolymer solution; (2) adding 0.9 parts of polyvinyl alcohol to 40 parts of deionized water and stirring at 85° C. for 2 h to obtain a polyvinyl alcohol solution; (3) mixing the phenolic resin prepolymer solution, the polyvinyl alcohol solution and 4 parts of nano-titanium dioxide with ultrasonic stirring for 0.5 h, and placing in an oven at 85° C. for 3 days to obtain a gel; (4) washing the gel with deionized water and ethanol in turn, and freeze-drying for 48 hours to obtain a precursor; (5) The precursor and potassium hydroxide in a mass ratio of 1:1 were mixed and ground, placed in a tube furnace, and treated at 750°C for 2 h in a N2 atmosphere; (6) washing with dilute HCl until neutral, drying, grinding, and sieving to obtain nano-titanium dioxide-loaded micron particles with a particle size of 10-100 μm. The micronized particles have pore sizes of 80-120 nm and 1-30 μm. Example 3 The preparation method of micron particles loaded with nano titanium dioxide is as follows: (1) heating and melting 1 part of phenol, adding 60 parts of sodium carbonate solution with a mass concentration of 0.05 g / L and keeping the temperature for 10 minutes, adding 1.4 parts of formaldehyde solution, heating to 70° C. within 15 minutes, keeping the temperature for 20 minutes, heating to 98° C., keeping reflux boiling for 45 minutes, and immediately cooling to 80° C. to obtain a phenolic resin prepolymer solution; (2) adding 1.0 part of polyvinyl alcohol to 40 parts of deionized water and stirring at 85° C. for 2 h to obtain a polyvinyl alcohol solution; (3) mixing the phenolic resin prepolymer solution, the polyvinyl alcohol solution and 4 parts of nano-titanium dioxide with ultrasonic stirring for 0.5 h, and placing in an oven at 85° C. for 3 days to obtain a gel; (4) washing the gel with deionized water and ethanol in turn, and freeze-drying for 48 hours to obtain a precursor; (5) The precursor and potassium hydroxide in a mass ratio of 1:1 were mixed and ground, placed in a tube furnace, and treated at 750°C for 2 h in a N2 atmosphere; (6) washing with dilute HCl until neutral, drying, grinding, and sieving to obtain nano-titanium dioxide-loaded micron particles with a particle size of 10-100 μm. The micronized particles have pore sizes of 80-120 nm and 1-30 μm. Example 4 The preparation method of micron particles loaded with nano titanium dioxide is as follows: (1) heating and melting 1 part of phenol, adding 60 parts of sodium carbonate solution with a mass concentration of 0.05 g / L and keeping the temperature for 10 minutes, adding 1.4 parts of formaldehyde solution, heating to 70° C. within 15 minutes, keeping the temperature for 20 minutes, heating to 98° C., keeping reflux boiling for 45 minutes, and immediately cooling to 80° C. to obtain a phenolic resin prepolymer solution; (2) adding 0.9 parts of polyvinyl alcohol to 40 parts of deionized water and stirring at 85° C. for 2 h to obtain a polyvinyl alcohol solution; (3) mixing the phenolic resin prepolymer solution, the polyvinyl alcohol solution and 2 parts of nano-titanium dioxide with ultrasonic stirring for 0.5 h, and placing in an oven at 85° C. for 3 days to obtain a gel; (4) washing the gel with deionized water and ethanol in turn, and freeze-drying for 48 hours to obtain a precursor; (5) The precursor and potassium hydroxide in a mass ratio of 1:1 were mixed and ground, placed in a tube furnace, and treated at 750°C for 2 h in a N2 atmosphere; (6) washing with dilute HCl until neutral, drying, grinding, and sieving to obtain nano-titanium dioxide-loaded micron particles with a particle size of 10-100 μm. The micronized particles have pore sizes of 80-120 nm and 1-30 μm. Example 5 The preparation method of micron particles loaded with nano titanium dioxide is as follows: (1) heating and melting 1 part of phenol, adding 60 parts of sodium carbonate solution with a mass concentration of 0.05 g / L and keeping the temperature for 10 minutes, adding 1.4 parts of formaldehyde solution, heating to 70° C. within 15 minutes, keeping the temperature for 20 minutes, heating to 98° C., keeping reflux boiling for 45 minutes, and immediately cooling to 80° C. to obtain a phenolic resin prepolymer solution; (2) adding 0.9 parts of polyvinyl alcohol to 40 parts of deionized water and stirring at 85° C. for 2 h to obtain a polyvinyl alcohol solution; (3) mixing the phenolic resin prepolymer solution, the polyvinyl alcohol solution and 3 parts of nano-titanium dioxide with ultrasonic stirring for 0.5 h, and placing in an oven at 85° C. for 3 days to obtain a gel; (4) washing the gel with deionized water and ethanol in turn, and freeze-drying for 48 hours to obtain a precursor; (5) The precursor and potassium hydroxide in a mass ratio of 1:1 were mixed and ground, placed in a tube furnace, and treated at 750°C for 2 h in a N2 atmosphere; (6) washing with dilute HCl until neutral, drying, grinding, and sieving to obtain nano-titanium dioxide-loaded micron particles with a particle size of 10-100 μm. The micronized particles have pore sizes of 80-120 nm and 1-30 μm. Example 6 The preparation method of micron particles loaded with nano titanium dioxide is as follows: (1) heating and melting 1 part of phenol, adding 60 parts of sodium carbonate solution with a mass concentration of 0.05 g / L and keeping the temperature for 10 minutes, adding 1.4 parts of formaldehyde solution, heating to 70° C. within 15 minutes, keeping the temperature for 20 minutes, heating to 98° C., keeping reflux boiling for 45 minutes, and immediately cooling to 80° C. to obtain a phenolic resin prepolymer solution; (2) adding 0.9 parts of polyvinyl alcohol to 40 parts of deionized water and stirring at 85° C. for 2 hours to obtain a polyvinyl alcohol solution; (3) mixing the phenolic resin prepolymer solution, the polyvinyl alcohol solution and 5 parts of nano-titanium dioxide with ultrasonic stirring for 0.5 h, and placing in an oven at 85° C. for 3 days to obtain a gel; (4) washing the gel with deionized water and ethanol in turn, and freeze-drying for 48 hours to obtain a precursor; (5) The precursor and potassium hydroxide in a mass ratio of 1:1 were mixed and ground, placed in a tube furnace, and treated at 750°C for 2 h in a N2 atmosphere; (6) washing with dilute HCl until neutral, drying, grinding, and sieving to obtain nano-titanium dioxide-loaded micron particles with a particle size of 10-100 μm. The micronized particles have pore sizes of 80-120 nm and 1-30 μm. The porosity, titanium dioxide loading and water washing stability-titanium dioxide retention rate of the nano-titanium dioxide-loaded micron particles were measured, and the results are shown in Table 1 below: Table 1 After comprehensive comparison of porosity and strength, Example 2, Example 3 and Example 6 were selected for subsequent tests. In the following embodiments, the aluminum alloy substrate includes the following components: Ni: 2.5%, Zn: 1.3%, Mg: 1.0%, Fe: 0.7%, B: 0.4%, other inevitable impurities: <0.2%, and the balance is Al. Example 7 A method for preparing a corrosion-resistant self-cleaning aluminum alloy, characterized in that it comprises the following steps: S1: 100 parts of an aluminum alloy substrate are heated until melted, and 5 parts of the nano-titanium dioxide-loaded micron particles prepared in Example 2 and 2 parts of yttrium oxide submicron fibers are added, wherein the diameter of the yttrium oxide submicron fibers is 100-300 nm and the length is 1-10 μm, and an electric mechanical stirrer is used for stirring; S2: Cast into a mold. Example 8 A method for preparing a corrosion-resistant self-cleaning aluminum alloy, characterized in that it comprises the following steps: S1: 100 parts of an aluminum alloy substrate are heated until melted, 8 parts of the nano-titanium dioxide-loaded micron particles prepared in Example 2 and 2 parts of yttrium oxide submicron fibers are added, wherein the diameter of the yttrium oxide submicron fibers is 100-300 nm and the length is 1-10 μm, and an electric mechanical stirrer is used for stirring; S2: Cast into a mold. Example 9 A method for preparing a corrosion-resistant self-cleaning aluminum alloy, characterized in that it comprises the following steps: S1: 100 parts of an aluminum alloy substrate are heated until it is melted, and 10 parts of the nano-titanium dioxide-loaded micron particles prepared in Example 2 and 2 parts of yttrium oxide submicron fibers are added, wherein the diameter of the yttrium oxide submicron fibers is 100-300 nm and the length is 1-10 μm, and an electric mechanical stirrer is used for stirring; S2: Cast into a mold. Example 10 A method for preparing a corrosion-resistant self-cleaning aluminum alloy, characterized in that it comprises the following steps: S1: 100 parts of an aluminum alloy substrate are heated until melted, 8 parts of the nano-titanium dioxide-loaded micron particles prepared in Example 2 and 1 part of yttrium oxide submicron fibers are added, wherein the diameter of the yttrium oxide submicron fibers is 100-300 nm and the length is 1-10 μm, and an electric mechanical stirrer is used for stirring; S2: Cast into a mold. Embodiment 11 A method for preparing a corrosion-resistant self-cleaning aluminum alloy, characterized in that it comprises the following steps: S1: 100 parts of an aluminum alloy substrate are heated until melted, 8 parts of the nano-titanium dioxide-loaded micron particles prepared in Example 2 and 3 parts of yttrium oxide submicron fibers are added, wherein the diameter of the yttrium oxide submicron fibers is 100-300 nm and the length is 1-10 μm, and an electric mechanical stirrer is used for stirring; S2: Cast into a mold. Example 12 A method for preparing a corrosion-resistant self-cleaning aluminum alloy, characterized in that it comprises the following steps: S1: 100 parts of an aluminum alloy substrate are heated until melted, 8 parts of the nano-titanium dioxide-loaded micron particles prepared in Example 3 and 2 parts of yttrium oxide submicron fibers are added, wherein the diameter of the yttrium oxide submicron fibers is 100-300 nm and the length is 1-10 μm, and an electric mechanical stirrer is used for stirring; S2: Cast into a mold. Embodiment 13 A method for preparing a corrosion-resistant self-cleaning aluminum alloy, characterized in that it comprises the following steps: S1: 100 parts of an aluminum alloy substrate are heated until melted, 8 parts of the nano-titanium dioxide-loaded micron particles prepared in Example 6 and 2 parts of yttrium oxide submicron fibers are added, wherein the diameter of the yttrium oxide submicron fibers is 100-300 nm and the length is 1-10 μm, and an electric mechanical stirrer is used for stirring; S2: Cast into a mold. Comparative Example 1 The difference between this embodiment and embodiment 8 is that no micron particles loaded with nano titanium dioxide are added. Specifically: A method for preparing a corrosion-resistant self-cleaning aluminum alloy, characterized in that it comprises the following steps: S1: 100 parts of an aluminum alloy substrate are heated until melted, 10 parts of yttrium oxide submicron fibers are added, the diameter of the yttrium oxide submicron fibers is 100-300 nm, and the length is 1-10 μm, and an electric mechanical stirrer is used for stirring; S2: Cast into a mold. Comparative Example 2 The difference between this embodiment and embodiment 8 is that yttrium oxide submicron fibers are not added. Specifically: A method for preparing a corrosion-resistant self-cleaning aluminum alloy, characterized in that it comprises the following steps: S1: 100 parts of aluminum alloy substrate are heated until melted, 10 parts of nano-titanium dioxide-loaded micron particles prepared in Example 2 are added, and an electric mechanical stirrer is used for stirring; S2: Cast into a mold. The hydrophobicity, self-cleaning and corrosion resistance of each embodiment were tested: Hydrophobicity test: The contact angle was recorded using a contact angle meter; Photocatalytic test: Determination of the photocatalytic degradation rate of Rhodamine B solution (5h); Corrosion resistance test: The static weight loss method was used to test the corrosion resistance of the samples of each embodiment. The samples were corroded for 5 hours at room temperature, a constant voltage of 3V, and a 3.5% Na Cl corrosion solution, and the weight loss rate (%) was measured. The results are shown in Table 2 below: Table 2

Claims

1. A method for preparing a corrosion-resistant self-cleaning aluminum alloy, characterized in that: The following steps are involved: S1: heating the aluminum alloy substrate until it is melted, adding micron particles loaded with nano-titanium dioxide and yttrium oxide submicron fibers, and stirring with an electric mechanical stirrer; S2: Cast into a mold.

2. The method for preparing a corrosion-resistant self-cleaning aluminum alloy according to claim 1, characterized in that: The aluminum alloy substrate comprises the following components: Ni: 2.5-2.7%, Zn: 1.0-2.0%, Mg: 0.6-1.1%, Fe: 0.5-1.0%, B: 0.2-0.5%, other inevitable impurities: <0.2%, and the balance is Al.

3. The method for preparing a corrosion-resistant self-cleaning aluminum alloy according to claim 1, characterized in that: The particle size of the micron particles loaded with nano titanium dioxide is 10-100 μm, and the micron particles have pore sizes of 80-120 nm and 1-30 μm.

4. The method for preparing a corrosion-resistant self-cleaning aluminum alloy according to claim 1, characterized in that: The yttrium oxide submicron fiber has a diameter of 100-300 nm and a length of 1-10 μm.

5. The method for preparing a corrosion-resistant self-cleaning aluminum alloy according to claim 1, characterized in that: The mass ratio of the aluminum alloy, the micron particles loaded with nano-titanium dioxide and the yttrium oxide submicron fibers is 100:(5-10):(1-3).

6. The method for preparing a corrosion-resistant self-cleaning aluminum alloy according to claim 1, characterized in that: The preparation method of the micron particles loaded with nano titanium dioxide is as follows: (1) heating and melting 1 part of phenol, adding 60 parts of sodium carbonate solution with a mass concentration of 0.05 g / L and keeping the temperature for 10 minutes, adding 1.4 parts of formaldehyde solution, heating to 70° C. within 15 minutes, keeping the temperature for 20 minutes, heating to 95-98° C., keeping reflux boiling for 45 minutes, and immediately cooling to 80° C. to obtain a phenolic resin prepolymer solution; (2) adding 0.8-1 parts of polyvinyl alcohol to 40 parts of deionized water, stirring at 85° C. for 2 hours to obtain a polyvinyl alcohol solution; (3) mixing the phenolic resin prepolymer solution, the polyvinyl alcohol solution and 2-5 parts of nano-titanium dioxide with ultrasonic stirring for 0.5 h, and placing in an oven at 85° C. for 3 days to obtain a gel; (4) washing the gel with deionized water and ethanol in turn, and freeze-drying for 48 hours to obtain a precursor; (5) The precursor and potassium hydroxide are mixed and ground, placed in a tube furnace, and treated at 750°C for 2 h in a N2 atmosphere; (6) washing with dilute HCl until neutral, drying, grinding, and sieving to obtain micron particles loaded with nano-titanium dioxide.

7. The method for preparing a corrosion-resistant self-cleaning aluminum alloy according to claim 6, characterized in that: The mass ratio of the precursor to potassium hydroxide is 1:

1.

8. A corrosion-resistant self-cleaning aluminum alloy prepared by the method according to any one of claims 1 to 7.